Lewis Rat Model of Experimental Autoimmune Encephalomyelitis. Issue 1 (13th February 2018) - Pitarokoili, Kalliopi; Ambrosius, Bjoern; Gold, Ralf
Abstract: In this unit, we describe in detail the most common methods used to break immunological tolerance for central myelin antigens and induce experimental autoimmune encephalomyelitis (EAE) in Lewis rats as an animal model of multiple sclerosis. The resulting disease course ranges from an acute monophasic disease to a chronic relapsing or chronic progressive course, which strongly resembles the human disease. These models enable the study of cellular and humoral autoimmunity against major antigenic epitopes of the myelin basic protein, myelin oligodendrocyte glycoprotein, or proteolipid protein. We provide an overview of common immunization protocols for induction of active and passive EAE, assessment and analysis of clinical score, preparation and purification of myelin basic protein, and derivation of neuroantigen‐specific rat T cell lines. Finally, we describe the major clinical characteristics of these models. © 2017 by John Wiley & Sons, Inc.